Histochemical and ultrastructure characterization of stem of Socratea exorrhiza (Mart.) H. Wendl. (Arecaceae) - Kikuchi, Tatiani Yuriko Pinheiro; Potiguara, Raimunda Conceição de Vilhena; Santos, Pedro Paulo dos (Boletim do Museu Paraense Emílio Goeldi - Ciências Naturais, 2007)
The aim of this work was to caracterize ergastics substances in stem of the Socratea exorrhiza (Mart.) H. Wendl., according to the point of view of the scanning electron microscopy. The histochemical analyses were carried with in natura samples from in the island of the Cumbu, Pará. The lugol was used to evidence the presence of starch grains; phenol crystals to silica; and acid clorídrico 10% + acid ascetic glacial, to crystals of calcium’s oxalate. The scanning electron microscopy showed triangular, ellipse and ellipsoidal starch grains, over there of calcium’s oxalate and silica crystals.